Prácticas de la basura y consumismo ¿Un habitus? - Cirett Galan, Diana Blanca (Pontificia Universidad Católica del Perú, 2025)
The relentless generation of urban solid waste, driven by the population growth of the last century and current consumption-disposal practices, represents a global municipal challenge due to its harmful effects. Its consequences impact various dimensions: health, public space, the environment, and society, among others. A comprehensive study was conducted in Guaymas and San Carlos, Sonora, Mexico, from 2019 to 2022, with the general objective of understanding how the meanings and practices around waste are shaped by gender identity, social class, sense of belonging, and public management in both public and private spaces. This article focuses on how consumerism affects the everyday waste-related practices of men and women in public spaces. The methodology was qualitative and descriptive, using the ethnographic method over five and a half months, with techniques such as observation, casual conversation, and semi-structured interviews conducted with ten informants and four key subjects related to urban solid waste. The findings revealed gender, social class, and belonging-related components connected to waste practices, as well as a differentiation of habitus between the two populations. In one group, there is a tendency to dispose of waste in public spaces, driven by habitual consumerism. This interaction is shaped by cultural, attitudinal, and public management factors—the latter influenced by the lack of policies that encourage individuals to adopt more responsible waste practices.

La incesante generación de residuos sólidos urbanos provocada por el incremento demográfico del último siglo y las prácticas de consumo-desecho actuales constituyen un reto municipal a nivel global por sus efectos nocivos. Sus consecuencias recaen sobre distintas dimensiones: la sanitaria, la pública, la ambiental y la social, entre otras. Se realizó una amplia investigación en Guaymas y en San Carlos, Sonora, México, de 2019 a 2022, cuyo objetivo general era entender cómo los significados y prácticas de la basura eran determinados por la identidad de género, las clases sociales, el sentido de pertenencia y la gestión pública en los espacios públicos y privados. Este artículo se centra en mostrar cómo el consumismo afecta las prácticas cotidianas de la basura de hombres y mujeres en los espacios públicos. La metodología fue cualitativa y descriptiva, utilizando el método etnográfico durante cinco meses y medio, con técnicas como la observación, la conversación casual y la entrevista semiestructurada aplicada a diez informantes y a cuatro sujetos claves relacionados con los residuos sólidos urbanos. Los hallazgos evidenciaron componentes de género, de clase social y de sentido de pertenencia relacionados con las prácticas de la basura y una diferenciación de habitus entre las dos poblaciones. Uno de ellos propicia disposiciones que contaminan los espacios públicos con desechos que son producto del consumismo habitual. Esa interacción está orientada por factores culturales, actitudinales y de gestión pública, este último causado por la falta de implementación de políticas que incidan en las personas en desarrollar prácticas más favorables con la basura.
Garbage Practices and Consumption ¿A Habitus?
Keywords: Waste practices; Socialization; Habitus; Habitual consumerism; Mexico; Prácticas de la basura; Socialización; Habitus; Consumismo habitual; México; https://purl.org/pe-repo/ocde/ford#2.07.01